Lack of Association between Folate-Receptor Autoantibodies and Neural-Tube Defects - MOLLOY, ANNE MARIE; SCOTT, JOHN MARTIN (My University, 2009)
Molloy AM, Quadros EV, Sequeira JM, Troendle JF, Scott JM, Kirke PN, Mills JL. `Lack of Association between Folate-Receptor Autoantibodies and Neural-Tube Defects? in New England Journal of Medicine, 361, (2), 2009, pp 152-160
PUBLISHED
Keywords: autoantibodies folate receptors